Meniscal attachment reconstruction combined with high tibial osteotomy in a patient with genu varum and posterior root injury of the lateral meniscus: a case report and brief review of the literature - Hou, Junhu; Ma, Xuepeng; Gao, Jie; Zeng, Zhaoyang; Xie, Xingwen; Li, Ning (Frontiers in Surgery, 2025)
Rationale: High tibial osteotomy (HTO) is primarily used to treat unicompartmental osteoarthritis. Despite its efficacy, there are strict indications, such as the need for the integrity of the lateral structures, especially the meniscus and cartilage. Here, we report a rare case of a posterior root tear of the lateral meniscus combined with genu varum, demonstrating how reconstructing the posterior root can expand the indications for HTO surgery. Patient concerns: A 58-year-old man complained of “pain in both knees for 5 years, aggravated in the right knee for 1 month.” Diagnoses: A preoperative diagnosis of lateral meniscus injury with genu varum was reached. Interventions: Under normal circumstances, this patient would not have been suitable for HTO. However, we reconstructed the lateral meniscus attachment point using the pull-out technique and then performed HTO. Outcomes: Postoperatively, the weightbearing line of the patient's lower limbs was successfully corrected. Lessons: Aggressive repair of damaged lateral compartment structures combined with HTO can expand the population suitable for knee preservation. Key points: This report describes the first case of posterior root injury to the lateral meniscus combined with knee varus deformity. The patient first underwent lateral meniscus root reconstruction using the pull-out technique, followed by a standard HTO surgery, resulting in satisfactory outcomes.